Enhancing undergraduates' critical thinking through research engagement: A practitioner research approach. (December 2020) - Yuan, Rui; Yang, Min; Stapleton, Paul
Highlights: Students receive systematic critical thinking (CT) training in a research project. Research engagement enhances students' CT skills and dispositions. Students transfer their newly developed CT to their own professional learning. Students need cognitive, social, and affective support in CT development. Abstract: It is generally acknowledged that research engagement provides students with a space to engage in a systematic process of inquiry which can foster their critical thinking (CT); however, to what extent and how it takes place remains under-investigated. This study, which, informed by the approach of practitioner research (PR), explores the CT development of a group of Bachelor of Education (English Language) undergraduate students by involving them as assistants in a research project. Drawing on data from semi-structured interviews with the participants and their written reflections, the study revealed that the students' research engagement in various forms (e.g., workshop learning, individual and collaborative analysis, group consultation, presentations and critiquing) enhanced their CT skills (i.e., analysis, categorization, and interpretation) and CT dispositions (i.e., flexibility, adaptiveness, and open-mindedness). The students also actively transferred the CT acquired in the project to their own disciplinary context, language teaching, which benefited their professional learning as future language teachers. The findings indicate that when designing and implementing courses, workshops, or projects aimed at enhancing students' CT, various dimensions need to be considered, including the degree of structured guidance, the collaborative arrangement, the integration of CT and content, as well as the students' motivation, learning styles and preferences.